Characteristics of Effective Teachers and Pertinent Effective Educational Factors According to the Teachers and Students Point of View in Schools of Nursing Kerman University of Medical Sciences - Tahereh Ramezani; Eshagh Dortaj Ravari (Kerman University of Medical Sciences, 2010)
Background & Objective : To assess the characteristics of a good teacher one must inquire the teachers opinion in addition to the students Hence this study was aimed to determine the characteristics of effective teachers and pertinent effective educational factors according to the nursing teachers and students point of view in schools of nursing in Kerman University of Medical Sciences   Methods : In t his descriptivecomparative study 358 students and 89 teachers from Kerman Bam Zarand and Jiroft schools of nursing participated Data was collected using a researchermade questionnaire which covered five domains   Results : A ccording to the students point of view interpersonal communication teaching skill personal characteristics evaluation skill and educational rules were priorities in order of importance whereas teachers gave priority to teaching skill educational rules evaluation skill personal characteristics and interpersonal communication The importance of interpersonal communication and personal characteristics according to the students opinion was significantly higher than what teachers believed (P=00001 and P=004 respectively) However the importance of teaching skill and educational rules was significantly higher in teachers opinion when compared to the students (P=00001 in both cases) Lack of enough time to study was the most important effective factor in teachers efficacy regarding the opinion of both teachers and students   Conclusion : Despite the big difference between the teachers and the students point of view it is suggested to consider improvement of communication skills together with modern teaching methods in teachers empowerment programs Educational managers should also direct their programs to gain a better background for studying learning and efficacy with a decrease in working hours